Performance Of Village-Owned Enterprises In Tanggetada Village, The Importance Of Tanggetada, Kolaka Regency - kastam, surya; R, La Ode Asrun Aziz; Septiana, Anis Ribcalia (Perkembangan Kajian Sosial, 2024)
The aim of this research is to find out and describe the performance of village-owned enterprises (BUMD) in Tanggetada Village, Tanggetada District, Kolaka Regency. Type of qualitative descriptive research. The research location is Tanggetada Village. The informants in this research consisted of the Tanggetada Village Head, village secretary, village treasurer, Chair of the Village Consultative Body (BPD), hamlet head, as well as the director, secretary, and treasurer of the Tanggetada Village-Owned Enterprise (Bumdes), including the Tanggetada Village community. Types and sources of data are primary data and secondary data. Based on the results of research regarding the performance of Bumdes on efficiency indicators, in terms of providing information to the public, it has not been implemented well. Bumdes and the village government are not thorough in conducting outreach to the community, so the Bumdes program is not yet fully known to the community. In terms of effectiveness, there is still a lack of public interest in purchasing Bumdes program businesses, coupled with business production, which has decreased due to limited capital. In the aspect of justice, community involvement in implementing the Bumdes program is still limited, as can be seen from the decline in sales production, coupled with sales prices that are quite different compared to other places. Meanwhile, in terms of responsiveness, the management of income from the Bumdes program to the village government is generally unknown to the community, and also the development of Bumdes' businesses has not been able to run well.